Studi Kelimpahan Aktinomisetes Tanah dan Hubungannya Terhadap Enzim Selulase, Amilase, Total Karbon dan Nitrogen Hutan Pasca Kebakaran Bukit Bangkirai Kalimantan Timur - Nurkanto, Arif (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRACTSoil Actinomycetes Population, Enzymes Activity, and its Relation with Carbon and NitrogenContent, in Bukit Bangkirai, East Kalimantan. Bukit Bangkirai is one of the tropical forest inIndonesia have been exposed with intense forest fire. The affected forest is subjectivelydivided into three level of damages, heavily damage forest (HD), low damage forest (LD) andcontrol (K). The objective of this research was to observe the abundance of Actinomyceteswhich have important role in ecological process. Through decompotition of organic materialsand nutriens cycle. Actinomycetes were isolated and enumerated by SDS-YE method. CFU/ gsoil (x 104) in K, HD and LD are 41,86 ± 25,52, 16,09 ± 5,70 and 18,96 ± 4,19 respectively. Amylaseand cellulase were determined by DNS method. Carbon and Nitrogen total were determinatedby CN analyzer. The different of amylase, cellulase activities and abundace of Actinomycetesbetween HD, LD, and Control plot were not significant. However, carbon and nitrogen totalare different. LD plot has the highest carbon and nitrogen total, followed by control and HDplot. There has no significant different among plot observed may indicate microbial communitiesof soil in Bukit Bangkirai have been recovered.Key words : actinomycetes, fire forest, amylase, cellulase, nitrogen total, carbon total